Bahasa Inggris - Elya Putri Pane; Yenny Risjani; Yunianta Yunianta; Gilang Drajat Maulana (Jurnal Penelitian Pendidikan IPA, 2023)
Indonesia is an archipelagic country with a water area of up to 5.9 million km2, where this water area is a habitat for marine diversity. One such diversity consists of macroalgae and microalgae. Diatoms are a group of microalgae with high diversity. Diatoms are one of a group of microscopic algae that can live in various habitats and are abundant in various ecosystems. Diatoms can be used as bioindicators of aquatic environmental quality. Navicula genus is an isolate that was successfully isolated from the waters of Pari Island, Kepulauan Seribu Regency. The total protein was analyzed by the Lowry-Follin method. The total fat content was determined by the soxhletation method. This genus Navicula contains a total protein content of 30,944 mg/L and a lipid content of 3.17%.